Respond to this Question
Similar Questions

Trigonometry Check
Simplify #3: [cosxsin(90x)sinx]/[cosxcos(180x)tanx] = [cosx(sin90cosxcos90sinx)sinx]/[cosx(cos180cosx+sinx180sinx)tanx] = [cosx((1)cosx(0)sinx)sinx]/[cosx((1)cosx+(0)sinx)tanx] = [cosxcosxsinx]/[cosx+cosxtanx] = 
PreCalc
Trigonometric Identities Prove: (tanx + secx 1)/(tanx  secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x  1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1  
maths  trigonometry
I've asked about this same question before, and someone gave me the way to finish, which I understand to some extent. I need help figuring out what they did in the second step though. How they got to the third step from the 
Calculus
Q: If y=sinx/(1+tanx), find value of x not greater than pi, corresponding to maxima or minima value of y. I have proceeded thus Equating dy/dx=0 we get{ (1+tanx)cosxsinx.sec^2 x}/(1+tanx)^2=0……..(A) Or cosx+sinx=sinx.sec^2 x 
Simplifying with Trigonometry Identities
Hi, I am a senior in High School having a really difficult time with two problems. I have to prove using the trigonometric identities that they equal each other but I am having a really hard time trying to get them to equal each 
Mathematics  Trigonometric Identities
Prove: (tanx)(sinx) / (tanx) + (sinx) = (tanx)  (sinx) / (tanx)(sinx) What I have so far: L.S. = (sinx / cosx) sinx / (sinx / cosx) + sinx = (sin^2x / cosx) / (sinx + (sinx) (cosx) / cosx) = (sin^2x / cosx) / (cosx / sinx + 
Mathematics  Trigonometric Identities
Prove: sinx + tanx = tanx (1 + cosx) What I have so far: LS: = sinx + tanx = sinx + (sinx / cosx) = (sinx) (cosx) + sinx / cos = tanx (cosx + sinx) I don't know what to do now 
Math
Im really struggling with these proving identities problems can somebody please show me how to do these? I'm only aloud to manipulate one side of the equation and it has to equal the other side of the equation at the end Problem 
Trigonometry.
( tanx/1cotx )+ (cotx/1tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated 
Math
Proving identity (sinx+tanx)/(cosx+1)=tanx RS: (sinx+(sinx/cosx))/(cosx+1) ((sinxcosx/cosx)+(sinx/cosx))x 1/(cosx+1) sinx(cosx+1)/cosx x 1/(cosx+1) sinx/cosx = tanx RS = LS How did sinxcosx/cosx turn to sinx(cosx+1)? 
precal
1/tanxsecx+ 1/tanx+secx=2tanx so this is what I did: =tanx+secx+tanxsecx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)(1/cosx) =sinx/cosx+ sinx /cosx= 2tanxI but I know this can't be correct because what I did doesn't end as a